ANALISIS SYA’IR LAM YAHTALIM DALAM KITAB MARAQI AL-‘UBUDIYYAH KARYA SYEKH NAWAWI AL-BANTANI: KAJIAN ‘ARUDH DAN QAWAFI - Muhamad Zidan Alida Putera; Muhammad ‘Alawi Muzhaffar; Muhammad Shafwan Ubaydillah (Afshaha: Jurnal Bahasa dan Sastra Arab, 2026)
The poem Lam Yahtalim is one of the six stanza poems contained in the book Maraaqi al-'Ubudiyyah by Sheikh Nawawi al-Bantani. In its composition, this poem uses a theory that regulates the structure of the formation of Arabic poetry called the science of ‘arudh and qawafi. This study focuses on the analysis of the verses of Lam Yahtalim’s poetry using both theories such as bahr, zihaf, ‘illat, qawafi letters and qawafi harakat. This study aims to describe the constituent elements in the form of tables and descriptions so that these elements can be easily identified. This study uses a descriptive-analytical research type by describing the data obtained and then analyzing it. The results of this study are that the poem Lam Yahtalim is composed using bahr basith with the presence of zihaf khabn in each ‘arudh and dharab without any ‘illat. From the qawafi review, all the verses of this poem have uniqueness with the same rawi muthlaq letters in the form of the letter nun and the washal letters using the letter ya', likewise the qafiyah harakat in this poem also has uniqueness with the same qafiyah harakat in each verse, namely the majra' harakat with the kasrah of the letter nun.